2012
DOI: 10.1021/jo202060k
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Direct Arylation of Polysubstituted Benzofurans

Abstract: An efficient access to 2-substituted 3-arylbenzofurans through a palladium-catalyzed C3 direct arylation of 2-substituted benzofurans with aryl bromides is described. The scope and limitation of this reaction was studied. The method tolerates a variety of functional groups on the aryl halide and has been successfully extended to polysubstituted benzofurans to obtain the corresponding 3-arylbenzofurans with good to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
78
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 78 publications
1
78
0
Order By: Relevance
“…Surprisingly, reaction of sesamol with methyl-10-undecanoate resulted in the 3-methylsubstituted product 5 b exclusively, and a similar 3-methylsubstituted product (5 e) was also observed with a simple terminal olefin. Note that the present method in conjunction with a previous report [21] will therefore allow the synthesis of unsymmetrical 2,3-disubstitutedbenzofurans. Interestingly, when allyl chloride was treated with 2-phenylphenol, 2-methyl-7-arylbenzofuran was obtained ( 5 l; Scheme 3).…”
mentioning
confidence: 78%
“…Surprisingly, reaction of sesamol with methyl-10-undecanoate resulted in the 3-methylsubstituted product 5 b exclusively, and a similar 3-methylsubstituted product (5 e) was also observed with a simple terminal olefin. Note that the present method in conjunction with a previous report [21] will therefore allow the synthesis of unsymmetrical 2,3-disubstitutedbenzofurans. Interestingly, when allyl chloride was treated with 2-phenylphenol, 2-methyl-7-arylbenzofuran was obtained ( 5 l; Scheme 3).…”
mentioning
confidence: 78%
“…These conditions allowed them to prepare a variety of 3-aryl-2-substituted benzo [b]furans in moderate to excellent yields, but proved to be unsuitable for the C-3 arylation of benzo[b]furans 2-substituted with an ethyl or a phenyl group. [66] It was also found that the PdA (96) with methyl 4-bromobenzoate gave compound 97 in 79% yield via a one-pot oxidation/arylation sequence (Scheme 45). [66] 3-Aryl-2-ketobenzofurans 99a and 99b were similarly prepared in high yield from secondary alcohols 98a and 98b (Figure 20), respectively, and the required aryl bromides.…”
Section: A C H T U N G T R E N N U N G (Hetero)arylation Of Furan Andmentioning
confidence: 99%
“…[66] 3-Aryl-2-ketobenzofurans 99a and 99b were similarly prepared in high yield from secondary alcohols 98a and 98b (Figure 20), respectively, and the required aryl bromides. [66] The oxidation step of these reactions could be explained by taking into account that aryl halides can be used as co-oxidants in Pd-catalyzed oxidation of primary and secondary alcohols.…”
Section: A C H T U N G T R E N N U N G (Hetero)arylation Of Furan Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Kappe [84] investigated the direct arylation using Fagnou's protocol [82] under microwave irradiation. Finally, palladium-catalyzed C-H arylations of thiophenes and furan derivatives were reported using thiophenes bearing SO 2 R substituents (2011) [85] by Doucet as well as polysubstituted benzofurans by Bertounesque [86].…”
Section: Thiophenes and Furans -Electron-rich Heteroarenesmentioning
confidence: 99%